Pemberdayaan Masyarakat Berbasis Ekonomi Kreatif Melalui Pengembangan Madu Kelulut Untuk Peningkatan Perekonomian Masyarakat Desa Rambahan Kec. Logas Tanah Darat Kab. Kuantan Singingi - M. Jaya Adiputra; Yuka Martlisda; Anwika Anwika; Meyla Suhendra; Arini Arini; Daeng Ayub (Unri Conference Series: Community Engagement, 2021)
This community empowerment program has the aim of providing knowledge and skills based on the creative economy in utilizing the local potential of kelulut honey in Rambahan Village, Kec. Logas Tanah Darat Kab. Kuantan Singingi, so that there is an improvement in terms of the community's economy to be better than before. This service activity was carried out in two activities, namely counseling on kelulut bee cultivation and testing of processed honey which went through three stages, the preparation stage, implementation and monitoring stage, and the final/evaluation stage. Implementation of activities using training and guidance and assistance. With material about cultivating kelulut bees using a stupor topping system and testing processed honey products to produce beverage products (honey syrup), beauty products (honey masks, honey soap), and health products (pure honey). The results of the service activities are considered successful and by the objectives and right on target. Through this activity, increase the knowledge and skills of the community in cultivating kelulut bees. The community can cultivate, starting from nurseries, maintenance, harvesting to marketing. The community has succeeded in cultivating bees and producing honey, as well as opportunities for processed honey products that can be developed. The community is keen to uncover the potential of processed honey which has economic value and becomes additional fields for honey farmers.